2013
DOI: 10.1007/s10803-013-1959-8
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Interhemispheric Connectivity in Childhood Autism Detected by Electroencephalographic Photic Driving Coherence

Abstract: The EEG coherence among 14 scalp points during intermittent photic stimulation at 11 fixed frequencies of 3-24 Hz was studied in 14 boys with autism, aged 6-14 years, with relatively intact verbal and intellectual functions, and 19 normally developing boys. The number of interhemispheric coherent connections pertaining to the 20 highest connections of each individual was significantly lower in autistic patients than in the control group at all the EEG beta frequencies corresponding to those of stimulation. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 39 publications
3
36
0
Order By: Relevance
“…In line with an emerging literature that consistently implicates cortical underconnectivity during various cognitive processes as a critical feature of ASD (e.g., Assaf et al, 2010; Damarla et al, 2010; Lazarev et al, 2013; Minshew & Keller, 2010), the findings from this study suggest that cortical underconnectivity may underlie joint attention impairments in ASD. This study also provides preliminary support for the current model of joint attention impairment of autism—one of a problematic integration between neural representations of self- and other-referenced information (Mundy et al, 2009, Mundy & Jarrold, 2010).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In line with an emerging literature that consistently implicates cortical underconnectivity during various cognitive processes as a critical feature of ASD (e.g., Assaf et al, 2010; Damarla et al, 2010; Lazarev et al, 2013; Minshew & Keller, 2010), the findings from this study suggest that cortical underconnectivity may underlie joint attention impairments in ASD. This study also provides preliminary support for the current model of joint attention impairment of autism—one of a problematic integration between neural representations of self- and other-referenced information (Mundy et al, 2009, Mundy & Jarrold, 2010).…”
Section: Discussionsupporting
confidence: 88%
“…Altered cortical connectivity in ASD has been posited to result from atypical brain overgrowth and neural pruning during critical periods of experience-dependent neurodevelopment (see Courchesne et al, 2005a for a review). Although there is a substantial body of literature indicative of cortical under-connectivity in individuals with ASD during a resting state (e.g., Cherkassy, Kana, Keller, & Just, 2006; Coben, Clarke, Hudspeth, & Barry, 2008; Lazarev, Pontes, Mitrofanov, & deAzevedo, 2013), language processing (Jones et al, 2010; Just et al, 2004; Kana, Keller, Cherskassky, Minshew, & Just, 2006), working memory (Koshino et al, 2005, 2008), affective processing (Wicker et al, 2008), perceptual processing (Darmala et al, 2010; Villalobos, Mizuno, Dahl, Kemmotsu, & Muller, 2005), and executive functioning (Just et al, 2007), there is also evidence of cortical over-connectivity during rest, imitation, and memory performance (e.g., Lynch et al, 2013; Uddin et al, 2013; Shih et al, 2010; Noonan et al, 2009). Studies have also reported both increased and decreased cortical connectivity in individuals with ASD that appears to be mediated by the frequency of neural oscillations and distance between cortical networks (e.g., Kitzbichler et al, in press).…”
mentioning
confidence: 99%
“…This weakness in inter-hemispheric synchronization could contribute to reduced integration of distributed cortical γ activity encoding sensory evidence. Similar inter-hemispheric synchronization differences have also been found in the β band in response to repetitive visual stimulation (Lazarev et al, 2015) and in low to moderate (<13 Hz) frequencies during picture identification (Catarino et al, 2013). Unfortunately, these inter-hemispheric studies did not establish the behavioral relevance of these differences.…”
Section: Oscillatory Organization Is Disrupted In Asdsupporting
confidence: 65%
“…This is particularly clear for the case of inter-hemispheric connections, for which a decrease in EEG/MEG functional connectivity has been reported in many studies [93,94,96,100,107,114,134]. A smaller number of studies report mixed long-range overconnectivity and underconnectivity [97] or increased long-range connectivity in infants [113] and adolescents [116,117], in adult rapid-eye movement (REM) sleep [108], and during a picture-naming task in adults [120].…”
Section: Resultsmentioning
confidence: 83%